Diversity of clinical phenotypes in a cohort of Han Chinese patients with PAX6 variants - Huang, Lijuan; Peng, Jiajia; Xie, Yan; Zhou, Yunyu; Wang, Xiaolin; Wang, Hui; Gui, Jingang; Li, Ningdong (Frontiers in Genetics, 2023)
The PAX6 gene plays an important role in ocular development. Mutations of the PAX6 gene may result in a series of ocular abnormalities, including congenital aniridia, anterior segment dysgenesis (ASD), progressive corneal opacification, glaucoma, and hypoplasia of the fovea and optic nerve, leading to reduced visual acuity and even blindness. This study aimed to describe the diversity of clinical features caused by PAX6 pathogenic variants in 45 Han Chinese patients from 23 unrelated families. All patients underwent detailed clinical assessment. Genetic testing was performed to identify pathogenic variations in the PAX6 gene by next-generation sequencing, minigene splicing assay, RT-qPCR, and long-range PCR. Twenty pathogenic variations were detected in the PAX6 gene from 12 pedigrees and 11 sporadic patients, of which 12 were previously reported and 8 were novel. The clinical phenotypes obtained as a result of the PAX6 gene mutations were complicated and vary among patients, even among those who carried the same variants. Genetic testing is helpful for differential diagnosis. Our genetic findings will expand the spectrum of pathogenic variations in the PAX6 gene. PAX6 pathogenic variants not only cause defects in ocular tissues, such as the iris and retina, but also lead to maldevelopment of the whole eye, resulting in microphthalmia.